2022
DOI: 10.3389/fmicb.2022.930477
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Analysis in Sichuan South-road Dark Tea Piled Center at Pile-Fermentation Metaphase and Insight Into Organoleptic Quality Development Mediated by Aspergillus niger M10

Abstract: Microbes are critical in the Sichuan South-road Dark Tea (SSDT) organoleptic quality development during pile-fermentation. Piled tea center at fermenting metaphase is crucial for the conversion of its quality components. In this study, we investigated the microbial community of piled SSDT center below the stacked tea surface of 15 cm (SSDTB), 50 cm (SSDTX), and 85 cm (SSDTH) on the second turning time of pile-fermentation, respectively. Results showed that SSDTH and SSDTB had a higher similarity in the microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Additionally, most of the GHs detected were located in the extracellular space, that means they can act directly on the tea leaves to stimulate chemical reactions. Regrettably, the GH genes detected in D. hansenii Y4 were not as abundant as those found in Aspergillus fungi (Ma et al, 2021;Zou et al, 2022Zou et al, , 2023.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Additionally, most of the GHs detected were located in the extracellular space, that means they can act directly on the tea leaves to stimulate chemical reactions. Regrettably, the GH genes detected in D. hansenii Y4 were not as abundant as those found in Aspergillus fungi (Ma et al, 2021;Zou et al, 2022Zou et al, , 2023.…”
Section: Discussionmentioning
confidence: 79%
“…In general, the transformation of the chemical component in SSDT during pile-fermentation always results from a synergistic effect of moist heat and microbial activity ( Zou et al, 2022 ), whereas, after excluding the effect of hygrothermal action used the control treatment, apparently, D. hansenii Y4 seriously reduced the contents of TPs and Caf, and altered the levels of catechin monomers in tea. Previous literature suggested that GHs, tannase, glycosyltransferases and so on could catalyze the hydrolysis of phenolic glycosides and phenolic esters, oxidation or polymerization of phenolic compounds, and destruction of the aromatic rings in phenolic compounds, thus significantly reducing the TPs levels in tea during fermentation ( Ma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations